KOMBINASI JENIS BIBIT DAN KONSENTRASI ZAT PENGATUR TUMBUH GIBERELIN TERHADAP PERTUMBUHAN TANAMAN PORANG (Amorphophallus oncophillus) - Fathurrahman Fathurrahman; Putri Istianingrum; Ni’mawati Sakinah (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2022)
Porang is a tuber plant that has the opportunity to be developed in Indonesia. Efforts have been made to increase the production potential of porang, including through nurseries. The purpose of this study was to determine the effect of tuber origin and concentration of gibberellin growth regulators on porang growth. The research was conducted in Wonosobo Village, Srono District, Banyuwangi Regency from August to November 2020. This study used a Randomized Block Design (RBD) with two factors, namely the origin of the seeds and the concentration of gibberellin growth regulators with three replications. Factors of seed origin consisted of tubers (B1) and air bulbs (B2) while ZPT gibberellin concentration factors were 1 ml/l (A1), 2 ml/l (A2), 3 ml/l (A3), 4 ml/l ( A4) and 5 ml/l (A5), resulting in 10 treatment combinations. Observational variables include shoot height and number of leaves. On the seedling origin factor, the B2 treatment was the highest in terms of the observed parameters of shoot height and number of leaves. In the ZPT gibberellin concentration factor, it was shown that factor A1 was the highest in the observed variable of shoot height 20 dap (days after planting), while in the variable number of leaves 50 dap, factors A4 and A5 had the highest number of leaves. The interaction of seed origin and gibberellin concentrations showed that factor B1A4 had the highest shoot height at 20 dap observations, while B1A5 had the highest number of leaves at 40 and 50 dap observations.